2019
DOI: 10.6087/kcse.151
|View full text |Cite
|
Sign up to set email alerts
|

Current and planned adoption of data sharing policies by editors of Korean scholarly journals

Abstract: Purpose: This study analyzed the present status of data sharing polices and attitudes towards such policies through a web-based survey of editors of scholarly journals published in Korea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 7 publications
0
16
0
1
Order By: Relevance
“…Whether to adopt a data sharing policy is the choice of the editor or publisher. Some editors are not interested in adopting a data sharing policy because they are worried about a possible decrease in the number of submissions and increased workload [1]. The main issue is that many journals stating that they had data sharing policies did not have actual statements of data availability in their articles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether to adopt a data sharing policy is the choice of the editor or publisher. Some editors are not interested in adopting a data sharing policy because they are worried about a possible decrease in the number of submissions and increased workload [1]. The main issue is that many journals stating that they had data sharing policies did not have actual statements of data availability in their articles.…”
Section: Discussionmentioning
confidence: 99%
“…Background/rationale: Data sharing, which is defined as the "practice of making data used for scholarly research available to other investigators" [1], has been introduced to increasingly many international journals to promote research integrity and reproducibility in scholarly journals. Several studies have been conducted on data sharing policies of journals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Korea, there are still only a few journals that have adopted a data-sharing policy. The results of a 2019 survey of 100 journals showed that 13 had adopted such a policy, with repository sites including Harvard Dataverse (2) and Mendeley Data (1) [21]. There is a Korean journal that mandates data sharing and peer-reviews data [22].…”
Section: Limitation and Suggestion For Further Developmentmentioning
confidence: 99%
“…Ale w prawie 77 proc. przypadków czasopisma tylko rekomendowały udostępnienie danych badawczych, nie obligując autorów do obowiązku ich udostępnienia (Kim, Yi, & Huh, 2019).…”
Section: Przegląd Badańunclassified